Anatomic vascular variations in sub-inguinal varicocelectomy - Orhan, I.; Cayan, S.; Karakeci, A. (Oxford Univ Press, 2015)
[Abstract Not Available]
31st Annual Meeting of the European-Society-of-Human-Reproduction-and-Embryology (ESHRE) -- JUN 14-17, 2015 -- Lisbon, PORTUGAL
Keywords: varicocele; microsurgical varicocelectomy; infertility